New Application of the ‘Core-Periphery Concept’ in Determining Local Development Strategy for Post-War Ukraine’s Recovery - Popov, Mykola; Komarovskyi, Ivan (Pressing Problems of Public Administration, 2024)
The success of regional development practices largely depends on the applicability of relevant foundational theories. A common approach to determining the theoretical basis for development programs is the application of the «core-periphery» concept. This concept is based on the thesis that in a spatial system, one can distinguish a core of development characterized by dynamic, competitive, and market-integrated production, and peripheral areas that are in a state of stagnation. According to this concept, the appropriate development strategy should focus on supporting those areas (the core) that have the necessary potential for growth. Taking into account the specifics of post-war recovery in Ukraine, building a development plan based on the «core-periphery» concept should include the following stages: identifying the differences in economic development levels of various territories; initiating the process of concentration based on regional centers to create dominant cores that will become growth poles; developing interactions between the elements of the «core-periphery» model based on innovation and the integration of Ukraine into the global market; and further developing the elements of the «core-periphery» model that potentially reduce spatial inequality for the periphery. The study shows that when applying the «core-periphery» model to Ukraine, it will be advisable initially to focus on replicating proven solutions, thus avoiding the costs associated with striving to find unique innovative solutions. Simultaneously, recognizing the existence and the connection between the core and the periphery will allow for the optimal allocation of available resources and the ability to focus on issues that are key to the specific territory. However, it is necessary to consider certain peculiarities of the «core-periphery» model: The existence of economic disparities and differences between the core and peripheral parts of the region. To support the development of the core as a priority, it is necessary to ensure the development of industry, access to resources, and infrastructure development. The uneven development of different regions of the country, which will lead to an uneven distribution of public goods within Ukraine.